FIELD CORRELATION BETWEEN PRECIPITATION-EL NINO RELATED VARIATION AND CORAL ?18O - Sri Yudawati Cahyarini; B. Suwargadi (Marine Geological Institute of Indonesia, 2007)
Coral ?18O from Maudulung-Indonesia was analyzed using Finnigan MAT 251. Using statistical analysis from KNMI database is obtained that the seasonal mean field correlation between coral ? 18OSOI shows strong correlation during October. Field correlation of precipitation-coral ? 18O shows opposite pattern between eastern Pacific and western Pacific during strong El Nino event. Keywords: coral ?18O, field correlation, El Niño, Maudulung Sumba. Kandungan ?18O dalam koral dari wilayah Maudulung, Sumba, dianalisis dengan menggunakan Finnigan MAT 251. Korelasi spasial antara ?18O dengan SOI dalam skala musiman tinggi selama bulan Oktober. Korelasi spasial ini dilakukan dengan menggunakan fasilitas analisa statistik dalam database KNMI. Korelasi spasial antara presipitasi- coral ?18O menunjukkan pola-pola yang berlawanan antara wilayah timur dan barat Pasifi selama El Niño. Kata kunci: Koral ?18O, korelasi spasial, El Niño, Maudulung Sumba.